Perlindungan Hukum Bagi Pekerja/Buruh Atas Pemberian Upah Kerja Dibawah Upah Minimum Menurut Perspektif Hukum Di Indonesia - Ndruru, Mei Rahmat Syah Elisabet; Jamba, Padrisan (SCIENTIA JOURNAL, 2023)
Welfare must be enjoyed for all people fairly and comprehensively. Welfare is alsoappropriate for workers. The legal dispute occurred in the city of Surabaya in the decision714/Pid.Sus/2022/PN.Sby. In this case, PT Rakuda Furniture paid wages below theminimum wage. The defendant has the duty of being responsible for the company'soperations in determining wages. What is the form of legal protection for workers/labourersfor work wages that are given below the minimum wage? giving wages below the minimumcan be subject to criminal sanctions based on Law No. 13 of 2003 concerningManpower.This study uses normative research, namely using direct studies of regulations.And using an approach to cases (Case Approach), and a legal approach to statutoryregulations (Statute Approach).The form of worker protection guarantee, namely Article 81number 63 in Law Number 11 of 2020 concerning Job Creation, emphasizes thatemployers who pay wages lower than the minimum wage are subject to criminal sanctionsin accordance with Wirjono Prodjodikoro's aim to protect workers' rights in receiving fairwages and to make lessons educating or improving people who commit crimes. Companiespaying wages below the minimum can be subject to criminal sanctions based on LawNumber 13 of 2003 concerning Manpower in Article 185 and Law Number 11 of 2020concerning Job Creation Article 88 E paragraph (2) states that Employers are prohibitedfrom paying wages lower than the minimum wage, this provision is burdensome criminalresponsibility is the responsibility of the management of the legal entity at PT RakudaFurniture so that companies that provide wages below the minimum can be subject tocriminal sanctions